PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Food & Beverage yang Terdapat Di Bursa Efek Indonesia Periode 2018-2022) - Atmojo, Kunto; Ratnawita, Ratnawita; Marbelia, Agustine Diana Putri (Aliansi : Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the influence of dividend policy, debt policy and profitability on company value in food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. To minimize a significant decline in share prices, management needs to adopt policies that can influence company value in front of investors. The phenomenon of the Food and Beverage industry has just slumped due to the global Covid-19 pandemic, the situation of the FB industry at the beginning of 2020 declined drastically due to the pandemic, andthe presence of the FB industry cannot be avoided by everyone. In this research, the author used secondary data in the form of financial reports of companies in the food and beverage sector listed on the Indonesia Stock Exchange for the period 2018 - 2022. The sampling technique was using the purposive sampling method. This research took a sample of 33 companies from a population of 17 companies in the food and beverage sector listed on the Indonesia Stock Exchange. The research method used in this research is a descriptive statistical method with classical test analysis, and multiple linear regression analysis using the Statistical Package for the Social Science (SPSS) version 16 program. Based on the description above, further research is needed to determine the consistency regarding factors that influence company value in food beverage sector companies. The results of this research show that dividend policy, debt policy and profitability have a positive effect on company value.Keywords: dividend policy, debt policy, profitability and firm value.